TOURISM AS A VICTIM OF CLIMATE CHANGE, ADAPTATION AND MITIGATION: CASE OF MALAYSIA AS A VULNERABLE DESTINATION - FARAHANI, BANAFSHEH MASTERI (ITB Journal Publisher, LPPM ITB, 2010)
Tourism in general and international tourism in specific as one of the main growing industry in the world has encountered many challenges in recent years. The issues include the terrorist attacks of September 11, 2001 global diseases like SARS, bird flu and H1N1, and the war in the Middle East as well as years of rising energy prices. Unlike natural diseases or terrorist attacks, climate change is not a short-term apprehension for tourism industry and its effect cannot be quickly forgotten. Climatic change consequences always have serious effects particularly if climate-sensitive tourism has major economic importance for the country. The objective of this paper is to study the impacts of climate change in Malaysia and the adaptation to control the probable decrease of tourist arrivals. The major climate change impacts are loss of natural attractions and species from destinations, increase of flooding risk damage to tourism infrastructure, loss of archaeological assets and other natural resources, increased coral bleaching, marine resource and aesthetics degradation in dive and snorkel destinations, coastal erosion, loss of beach area, and higher costs to protect and maintain waterfronts. The adaptations includes water (management, quality, availability), agriculture, fisheries (food security), energy (supply and distribution), human health (malaria, dengue, asthma), marine and terrestrial biodiversity and infrastructure and settlement.